DUALISME MEKANISME PENGUJIAN PERATURAN DESA - Eryanto Siagian; Eddy Asnawi; Bahrun Azmi (Fakultas Hukum Universitas Borneo Tarakan, 2021)
AbstractThe state recognizes the existence of the village as the lowest unit in the Indonesian government system. The village has a very large influence on the success of the administration of the government system so that the Act guarantees the recognition and protection of the village's traditional rights and provides freedom to organize its own government system. However, in practice, legal problems arise, namely regarding the position of village regulations and the mechanism for canceling village regulations because in their provisions the cancellation of village regulations is not found in Law Number 6 of 2014 and is instead regulated in PP. 43 of 2014. The purpose of writing this scientific paper is to analyze the position of village regulations in statutory regulations, the mechanism for canceling village regulations and the legal implications of village regulations being canceled by the Regent/Mayor. The research method that will be used in this study is a normative legal research method that will examine based on the rules, principles and norms contained in the legislation.Keywords: Village; Village Regulations; Village Autonomy; Laws and Regulations; Cancellation of Village RegulationsAbstrakNegara mengakui keberadaan desa sebagai unit terendah dalam sistem pemerintahan Indonesia. Desa memiliki pengaruh yang sangat besar akan keberhasilan penyelenggaraan sistem pemerintahan sehingga Undang-Undang menjamin pengakuan dan perlindungan terhadap hak-hak tradisional desa serta memberikan kebebasan dalam menyelenggarakan sistem pemerintahan sendiri. Namun dalam praktiknya, problematika hukum muncul yaitu terkait kedudukan peraturan desa dan mekanisme pembatalan peraturan desa karena dalam ketentuannya pembatalan peraturan desa tidak ditemukan didalam Undang-Undang Nomor 6 Tahun 2014 dan justru diatur alam PP No. 43 Tahun 2014. Tujuan penulisan karya ilmiah ini adalah untuk menganalisa kedudukan peraturan desa dalam peraturan perundang-undangan, mekanisme pembatalan peraturan desa dan bagaimana implikasi hukum peraturan desa yang dibatalkan oleh Bupati/Walikota. Metode penelitian yang akan digunakan dalam penelitian ini adalah metode penelitian hukum normatif yang akan mengkaji berdasarkan kaidah, asas dan norma-norma yang tertuang didalam peraturan perundang-undangan.Kata Kunci: Desa; Peraturan Desa; Otonomi Desa; Peraturan Perundang-Undang; Pembatalan Peraturan Desa.